A fatal case of poisoning related to new cathinone designer drugs, 4-methoxy PV8, PV9, and 4-methoxy PV9, and a dissociative agent, diphenidine. Issue 5 (September 2015) - Kudo, Keiko; Usumoto, Yosuke; Kikura-Hanajiri, Ruri; Sameshima, Naomi; Tsuji, Akiko; Ikeda, Noriaki
Highlights This is the first case report which describes a fatal poisoning case related to 3 cathinone derivatives, 4-methoxy PV8, PV9, and 4-methoxy PV9, and a dissociative agent, diphenidine. Sensitive and reliable method to determine all these drugs together with 3 benzodiazepines and their metabolites in biological fluids was established by LC–MS/MS using the modified QuEChERS method.